The Effect Of Substitution Of Soy Milk On The Quality Of The Mud Cake - Rahma, Silvani; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
This research is motivated because there is no research on mud cakes with soy milk substitution. This study aims to analyze the effect of soy milk substitution as much as 25%, 50%, and 75% on the quality of the mud cake which includes shape, color, aroma, texture and taste. This type of research is a pure experiment with three repetitions carried out in August 2021. The type of data in this study is primary data sourced from 3 expert panelists by answering the organoleptic test format. The data that has been obtained is then tabulated in tabular form and analysis of variance (ANOVA) is carried out, if Fcount > Ftable then it is continued with Duncan's test. The results showed that the substitution of soy milk had an effect on the quality of the texture and taste of the kue lumpur and there was no effect on the quality of the shape, color and aroma of the kue lumpur. The best results based on the organoleptic test were found in the X3 treatment with 75% soy milk substitution.